Deposition of hBN+Cu layer through electrical discharge process using green compact electrode. Issue 9 (4th July 2019) - Tyagi, Rashi; Pandey, Kshitij; Das, Alok Kumar; Mandal, Amitava
ABSTRACT: In the current investigation, solid-lubricant surfaces were prepared onto the mild steel work piece by means of electrical discharge coating process in electrical discharge machine (EDM). Hexagonal boron nitride (hBN) and copper (Cu) powder-based green compact electrodes, prepared in hot mounting press were used as an EDM tool. The loosely bonded material particles from the compact tool were transported to the mild steel surface. With the change of process parameters (powder mixture ratio, duty factor, and peak current), the variation in surface morphology, micro-hardness and tribological properties of hBN-Cu coating layer has been discussed. Following the investigation, field emission scanning electron microscopic (FESEM) images of coating indicated fewer gaps and pores for the powder lubricant mixing ratio of hBN: Cu/50:50, peak current value of 10 A and duty factor value of 70%. X-ray diffraction plot composed of prominent peaks of BN, Cu, along with Fe2 O3 (intermetallic compound). Micro-hardness value of lubricant surfaces drastically reduced to the minimum of 75.76 HV (coating layer) from 180 HV (substrate). Moreover, pin on disk tribological test indicated the lubrication effect of hBN particles by revealing a major drop in wear value from 95.75 µm (work piece) to 1.52 µm (coating) and friction coefficient from 0.9 (work piece) to 0.1 (coating).